Struktur Modal, Profitabilitas, Likuiditas, Leverage dan Financial Distress - Dini, Siti; Selvia, Selvia; Octavia, Venny; Sidebang, Cyndi Natalia Br (E-Jurnal Akuntansi; Vol 31 No 11 (2021), 2021)
This study aims to determine the effect of capital structure, profitability, liquidity and leverage in predicting the potential for financial distress. This research includes causative research to see the relationship between variables. The data used is quantitative data from the Indonesia Stock Exchange. The research population is large trading companies on the IDX for the 2017-2019 period. The sample used as many as 33 companies. This research uses binary logistic regression analysis technique with SPSS 26.0 tool. The results showed that capital structure with DER proxies, profitability with ROA proxies and liquidity with CR proxies had no effect on financial distress. Meanwhile, leverage with DAR proxy has a significant positive effect on financial distress. Keywords : Financial Distress; Capital Structure; Profitability; Liquidity and Leverage.